EXPLORATION OF NOVICE STUDENTS IN PROBLEM SOLVING OF STATIC FLUID PHYSICS MATERIALS - Revnika Faizah; Sentot Kusairi; Arif Hidayat; Supriono Koes; Lari Andres Sanjaya; Astrini Dewi Kusumawati (EDUSAINS, 2023)
One essential ability in physics is problem-solving ability. Problem-solving and physics are inseparable. This research aims to reveal how students solve physics problems. This research is quantitative descriptive research, namely describing students' problem-solving abilities in Static Fluid material. This research was conducted on 28 Physics education students at one of the State Universities in East Java. Data was collected through tests and in-depth interviews. The research instrument was two test items on statistical fluid problem-solving. The results show that the students' physics problem-solving abilities are still in the beginner category. Learners need to work on solving problems correctly with incomplete problem-solving aspects. The interviews showed that students' difficulties in the problem-solving process were mainly in determining the physics approach to use and bringing the physics approach to specific conditions. This analysis can help further studies of improving novice physics problem-solving abilities